Photophysical Properties of Porphyrin Dendrimers as Red Light-Emitters for Organic Light-Emitting Diode (OLED) - Promarak*, Vinich; Pankwaung, Oradee (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
We report on the investigation of photophysical properties of the free-base and metal chelated porphyrins bearing bulky stilbene dendron substituents at the meso-positions. The free-base and zinc chelated porphyrins emitted a red fluorescence in solution and solid state, while the copper derivatives were non-luminescent. The zinc porphyrin derivative with a G-1 stilbene dendron substituted on the meso-positions emitted the best red colour with a colour chromaticity close to a red colour using in a full-colour display screen. Upon excitation of the dendron units in dichloromethane an intramolecular energy transfer took place from the dendron units to the porphyrin core. Keywords: porphyrin, dendrimer, red-light emitter, organic light-emitting diodes (OLED) Corresponding author: E-mail: pvinich@sci.ubu.ac.th